Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijerph18062925
|View full text |Cite
|
Sign up to set email alerts
|

Food Neophobia and Consumer Choices within Vietnamese Menu in a Polish Cohort Study

Abstract: One of the factors influencing consumer food choices is food neophobia (FN), described as a reluctance to try novel or unknown food products. The aim of the study was to determine the influence of FN on food choices in young Polish respondents through a web-based choice experiment with Vietnamese restaurant menu. The choice experiment was conducted using a Computer-Assisted Web Interview (CAWI) method in a sample of 601 young adults, while using a developed Vietnamese restaurant menu. For the dishes, neophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
1
8
0
1
Order By: Relevance
“…In the absence of such an association, respondents with a high level of food neophobia chose dishes with animal-based components, which was observed for starters and main courses, less often than those with a low level of food neophobia. The general association between food neophobia and the choice of dishes with components of non-neophobic potential (familiar to the studied sample) was also stated in previous studies [ 16 , 17 ]. Similarly, associations between food neophobia and the reduced intake of fruits and vegetables [ 42 ], as well as low diet variety, have been well established [ 43 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In the absence of such an association, respondents with a high level of food neophobia chose dishes with animal-based components, which was observed for starters and main courses, less often than those with a low level of food neophobia. The general association between food neophobia and the choice of dishes with components of non-neophobic potential (familiar to the studied sample) was also stated in previous studies [ 16 , 17 ]. Similarly, associations between food neophobia and the reduced intake of fruits and vegetables [ 42 ], as well as low diet variety, have been well established [ 43 ].…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that food neophobia seemed to influence food choices in the Polish population, both in Italian restaurants (highly familiar to Polish consumers) [ 16 ] and Vietnamese restaurants (relatively unknown to Polish consumers) [ 17 ]. However, familiarity with a specific cuisine may be another important determinant of restaurant meal choice, as familiar food products are generally preferred over unfamiliar ones [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eating behavior is determined by many factors, including biological, anthropological, economic, psychological, socio-cultural, and home-related factors, and their influences compete, reinforce, and interact with each other and are shaped by the individual situation of the family [ 20 ].…”
Section: Food Neophobiamentioning
confidence: 99%
“…Los resultados guardan consistencia con otras investigaciones que han empleado la ENA en diferentes contextos en México (Salgado et al, 2016;Bernal-Gil et al, 2020) Otro aspecto a destacar es que el estudio fue llevado a cabo en tiempos de la pandemia de COVID-19, lo que sugeriría que al menos en este sector de la población, la epidemia causada por el virus SARS-CoV-2 no ha afectado significativamente en los niveles de miedo o rechazo de alimentos nuevos extraños entre algunos sectores de la población joven del país. Guzek et al (2021) reportaron también que algunos consumidores jóvenes presentaron bajos niveles de neofobia alimentaria en tiempos de COVID-19.…”
Section: Neofobia Alimentaria Estudiantes Universitariosunclassified